Literature review: Factors Influencing The Incidence of Obesity in Adolescents in Pandemic Times - Rukmana, Olivia Meida; Nashtiti, Diyah Sufi; Apriningsih, Apriningsih (Sekolah Tinggi Ilmu Kesehatan Putra Abadi Langkat, 2021)
The spread of the Covid-19 virus can’t be denied has provided a sudden and fundamental change in habits and lifestyle. The number of activities at home alone, raises concerns about the emergence of health problems, namely obesity. Obesity or commonly known as obesity is a problem that is quite troubling among adolescents, especially teenagers. Adolescents who are obese, later in adulthood tend to be obese. The goal of the study was to obtain data on factors associated with the incidence of obesity in adolescents during pandemic times. The method used is literature review. A systematic search of previous research in the form of journals to identify all published literature using relevant keywords. Based on the results of the review of articles from several studies there are several factors that affect the occurrence of obesity in adolescents during the pandemic, including; Physical activity, diet, consumption of junk food and fast food, intensity of social media use and parental history.